PENGARUH PPN DAN PPH TERHADAP PENDAPATAN PAJAK PUSAT - Rano Karno; Marthinus Ismail (Fakultas Ekonomi Universitas Advent Indonesia, 2021)
The Directorate General of Taxes (DGT) or Central Tax is the government's partner in implementing tax reform in Indonesia to increase tax revenues which will be managed by the government and set forth in the APBN. The purpose of this study was to determine the effect of VAT and PPh on central tax revenues based on secondary data from the 2000-2019 DGT annual report. The research method used is a confirmation method that is processed from quantitative data. Analysis of the data used is descriptive analysis, correlation coefficient, coefficient of determination, significance test and simple regression. The results showed that the average increase in VAT receipts from year to year was Rp.258.8 million, while the average increase in income tax revenues was Rp.376.5 million, and the average increase in central tax revenues was Rp. 657.1 million. VAT and PPh have an influence on central tax revenues. The significance test shows that Ho is accepted (sig. 0.00 > 0.05) so that VAT and PPh have a significant effect on central tax revenue.